Computational Aesthetics in Improving Regional Election Mascot Branding Using Hue Saturation Value Method - Hasbullah, Hasbullah; Swandi, I Wayan; Udayana, Anak Agung Gde Bagus; Dewi, Alit Kumala (Universitas Bumigora Mataram-Lombok, 2025)
The digital era has a visual appeal that plays a crucial role in strengthening identity and public involvement in political campaigns, particularly in the election of the regional head of Mataram City. The role of visual mascots is important in attracting public attention. Through the intensity of color in digital media, it can attract attention and persuade the public to like it, thus building trust in the branding of the Mataram city election. However, the deviation value from the dominant color intensity in the Mataram City election mascot on the computer screen remains unclear. The core issue lies in identifying the exact value of the color intensity in the mascot design, which serves as a digital aesthetic element in strengthening the branding identity of the Mataram City election. This study aims to analyze the color intensity of the mascot design as a reflective attraction in the regional political campaign in Mataram City. The method used is Hue, Saturation, Value (HSV), with cultural and psychological color analysis image processing techniques to attract public participation and perception. The results of the study indicate that the color intensity based on HSV segmentation increases. The average color Hue has a deviation of 0.0319, Saturation has a deviation of 0.0255, and Value has a deviation of 0.9409, all of which are attributed to the dominant color in the mascot design on the computer screen. The HSV color intensity in the design of the Mataram city election mascot, especially on the screen, has an average value that intersects with each other, resulting in unity and forming an aesthetically pleasing visual. In conclusion, the brightness of the dominant color is a crucial aspect of creating aesthetic elements that capture the audience's attention. The implications of the study's results serve as a basic reference for creating graphic designs using computer technology.